Insulin resistance and racial disparities in breast cancer prognosis: a multi-center cohort study. Issue 12 (2nd November 2022) - Gallagher, Emily J; Greco, Giampaolo; Lin, Sylvia; Yagnik, Radhi; Feldman, Sheldon M; Port, Elisa; Friedman, Neil B; Boolbol, Susan K; Killelea, Brigid; Pilewskie, Melissa; Choi, Lydia; LeRoith, Derek; et al.
Abstract : The survival for breast cancer (BC) is improving but remains lower in Black women than White women. A number of factors potentially drive the racial differences in BC outcomes. The aim of our study was to determine if insulin resistance (defined as homeostatic model assessment for insulin resistance (HOMA-IR)), mediated part of the relationship between race and BC prognosis (defined by the improved Nottingham prognostic index (iNPI)). We performed a cross-sectional study, recruiting self-identified Black and White women with newly diagnosed primary invasive BC from 10 US hospitals between March 2013 and February 2020. Survey, anthropometric, laboratory, and tumor pathology data were gathered, and we compared the results between Black and White women. We calculated HOMA-IR as well as iNPI scores and examined the associations between HOMA-IR and iNPI. After exclusions, the final cohort was 1206: 911 (76%) White and 295 (24%) Black women. Metabolic syndrome and insulin resistance were more common in Black than White women. Black women had less lobular BC, three times more triple-negative BC, and BCs with higher stage and iNPI scores than White women ( P < 0.001 for all comparisons). Fewer Black women had BC genetic testing performed. HOMA-IR mediated part of the association between race and iNPI, particularly in BCs that carried a good prognosis and were hormone receptor (HR)-positive. Higher HOMA-IR scores were associated with progesterone receptor-negative BC in White women but not Black women. Overall, our results suggest that HOMA-IR contributes to the racial disparities in BC outcomes, particularly for women with HR-positive BCs.